Reactivity of Sedimentary and Metamorphic Limestones of Different Particle Sizes under Controlled Conditions - Soratto, Rogério P. [UNESP]; Crusciol, Carlos A. C. [UNESP]; Fernandes, Adalton M. [UNESP]; Cantarella, Heitor; Quaggio, José A.; Vitti, Godofredo C. (Taylor & Francis, 2019)
The efficiency of limestone in amending soil acidity is primarily based on the particle size and the neutralization value of the ground rock, but the origin of the rock can also affect its reactivity. The aim of this work was to evaluate, under controlled conditions, the efficiency of the reactivity of sedimentary limestones of different particle sizes in neutralizing soil acidity. The experiment was conducted using a clayey and a sandy soil, and the treatments consisted of four samples of a sedimentary limestone (with the same neutralization values but different particle sizes), two metamorphic limestones and an untreated control. In the first months of incubation, the sedimentary limestones demonstrated higher soil amelioration abilities than the metamorphic limestones, but all samples used in the study achieved the goal of neutralizing soil acidity to desired values: a base saturation (BS) of ~70% and a pH > 6.0. In sedimentary limestones, the availability of calcium (Ca) and magnesium (Mg) was more closely related to the levels of Ca oxide (CaO) in the amendment than to the size of the particles. The results of this study suggest that the currently used equation may underestimate the reactivity of certain limestones.
Keywords: friability; Liming material; parent material; particle size; sedimentary rock